Mapping a winning strategy : developing and executing a successful strategy in turbulent markets - Baaij, Marc; Reinmoeller, Patrick (Emerald Publishing Limited, 2018)
In an increasingly connected world experiencing acceleratinglevels of technological disruption, the strategic challenges for businessleaders are greater than ever before, and conventional approaches to strategyare unable to contend with today's VUCA (volatile, uncertain, complex andambiguous) business environment. A new approach to strategic decision-making isrequired to motivate and mobilize stakeholders to achieve the businesssoverarching goals, such as making a profit and delivering on people- and planet-relatedobjectives. "Mappinga Winning Strategy" introducesa new mapping method for creating and executing an effective business strategy.This method uses visual maps to engage colleagues throughout the organization,ensuring that every stakeholders voice is considered by avoiding a top-downapproach. It also enables business leaders to identify the strategic issuesthey face without distraction, so that a clear path is formed towards the beststrategic plan. By mapping out the most effective strategy, organizations cananticipate and manage roadblocks to strategic change and make winning andwell-executed operational choices.